1995
DOI: 10.1088/0031-9155/40/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of ocular fundus tissues-an in vitro study using the double-integrating-sphere technique and inverse Monte Carlo simulation

Abstract: Various models have been published calculating the light transport at the ocular fundus either for interpretation of in vivo reflectance measurements or for the prediction of photocoagulation effects. All these models took the absorption spectra of the pigments located at the ocular fundus, melanin, haemoglobin, xanthophyll, and the photoreceptor pigments, into account. However, light scattering inside the single fundus layers has not been investigated in detail and was, therefore, neglected in the calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
186
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(196 citation statements)
references
References 24 publications
9
186
0
1
Order By: Relevance
“…4(a)] specifically imaged five individual retinal vessels and the RPE due to strong optical absorption of hemoglobin and melanin. Unlike clearly resolved multiple retinal layers in the SD-OCT B-scan, other anatomic layers except for the vasculature and the RPE were invisible in the PAOM B-scan due to their low optical absorption coefficients 24 and poor axial resolution in the PAOM. 4 The 1 When we compare the PAOM and FA-SLO images, much finer details of the retinal capillaries can be observed in the FA-SLO image than in the PAOM image.…”
Section: Resultsmentioning
confidence: 91%
“…4(a)] specifically imaged five individual retinal vessels and the RPE due to strong optical absorption of hemoglobin and melanin. Unlike clearly resolved multiple retinal layers in the SD-OCT B-scan, other anatomic layers except for the vasculature and the RPE were invisible in the PAOM B-scan due to their low optical absorption coefficients 24 and poor axial resolution in the PAOM. 4 The 1 When we compare the PAOM and FA-SLO images, much finer details of the retinal capillaries can be observed in the FA-SLO image than in the PAOM image.…”
Section: Resultsmentioning
confidence: 91%
“…This way, image degradation by the inhomogeneous optical properties of the retinal neuronal elements, which scatter light as it travels from the inner to the outer retina (Hammer, Roggan, Schweitzer, & Muller, 1995), is reduced.…”
Section: Neural Glial and Epithelial Structuresmentioning
confidence: 99%
“…Ocular fundus tissues have been extensively studied by Hammer et al [7], who reported in their paper the optical properties summarized in Table I. shape and size of the molecules, interaction among other molecules, constraints due to membranes, and so forth.…”
Section: Iia Theoretical Backgroundmentioning
confidence: 99%